Global Health Education in US Pediatric Critical Care Medicine Fellowships - Adeolu Aromolaran; Brittany Murray; Cynthia Sinha; Zhulin He; Mary L. DeAlmeida (Journal of Medical Education and Curricular Development)
Background Global health (GH) education is of growing interest and importance among pediatric trainees, including those pursuing pediatric critical care medicine (PCCM) training. Despite this, opportunities for formal GH training in US PCCM fellowships are limited. Objective This study aims to describe the GH curricula at US PCCM fellowships, barriers to GH education expansion, and fellow attitudes toward GH. Methods This study was a cross-sectional survey of program directors (PDs) and fellows from PCCM fellowships regarding currently available GH education at their institutions. Results We obtained data from 48 of 76 (63%) PCCM fellowship PDs and 60 PCCM fellows. Of responding programs, 9 (19%) offered a formal GH track, 28 (58%) offered GH opportunities but did not have a formal track, and 11 (23%) offered no GH opportunities. Programs that offered GH training had more fellows ( P  = .02) and GH faculty ( P  < .01) than those with no GH training. The most common GH-related offerings were sporadic GH lectures (76%), international clinical experiences (65%), and a GH-related scholarly project (51%). The significant barriers to the expansion of GH training were lack of funding, scheduling considerations, and lack of faculty mentorship. Conclusions GH education is available for PCCM fellows in the majority of training programs; however, this education is highly variable and often incomplete. While there is interest from both faculty and fellows in making this education more robust, significant institutional barriers persist. Addressing these barriers will be essential to promoting and enhancing GH education in PCCM fellowships.